Deregulated expression and activity of Farnesyl Diphosphate Synthase (FDPS) in Glioblastoma. Issue 1 (December 2017) - Abate, Mario; Laezza, Chiara; Pisanti, Simona; Torelli, Giovanni; Seneca, Vincenzo; Catapano, Giuseppe; Montella, Francesco; Ranieri, Roberta; Notarnicola, Maria; Gazzerro, Patrizia; Bifulco, Maurizio; Ciaglia, Elena
Abstract Glioblastoma (GBM), the most aggressive brain cancer, is highly dependent on the mevalonate (MVA) pathway for the synthesis of lipid moieties critical for cell proliferation but the function and regulation of key intermediate enzymes like farnesyl-diphosphate synthase (FDPS), up to now, remained unknown. A deregulated expression and activity of FDPS was the central research idea of the present study. FDPS mRNA, protein and enzyme activity were analyzed in a cohort of stage III-IV glioma patients (N = 49) and primary derived cells. FDPS silencing helped to clarify its function in the maintenance of malignant phenotype. Interestingly, compared to tumor-free peripheral (TFB) brain and normal human astrocytes (NHA), FDPS protein expression and enzyme activity were detected at high degree in tumor mass where a correlation with canonical oncogenic signaling pathways such as STAT3, ERK and AKT was also documented. Further, FDPS knockdown in U87 and GBM primary cells but not in NHA, enhanced apoptosis. With the effort to develop a more refined map of the connectivity between signal transduction pathways and metabolic networks in cancer FDPS as a new candidate metabolic oncogene in glioblastoma, might suggest to further target MVA pathway as valid therapeutic tool.